Difference between revisions of "2006 AIME II Problems/Problem 6"
Expilncalc (talk | contribs) (→Elegant Solution: Changed variable name.) |
(→Problem) |
||
(8 intermediate revisions by 6 users not shown) | |||
Line 1: | Line 1: | ||
== Problem == | == Problem == | ||
− | + | Square <math> ABCD </math> has sides of length 1. Points <math> E </math> and <math> F </math> are on <math> \overline{BC} </math> and <math> \overline{CD}, </math> respectively, so that <math> \triangle AEF </math> is equilateral. A square with vertex <math> B </math> has sides that are parallel to those of <math> ABCD </math> and a vertex on <math> \overline{AE}. </math> The length of a side of this smaller square is <math>\frac{a-\sqrt{b}}{c}, </math> where <math> a, b, </math> and <math> c </math> are positive integers and <math> b</math> is not divisible by the square of any prime. Find <math> a+b+c. </math> | |
== Solution 1 == | == Solution 1 == | ||
Line 34: | Line 34: | ||
Call the vertices of the new square A', B', C', and D', in relation to the vertices of <math>ABCD</math>, and define <math>s</math> to be one of the sides of that square. Since the sides are [[parallel]], by [[corresponding angles]] and AA~ we know that triangles <math>AA'D'</math> and <math>D'C'E</math> are similar. Thus, the sides are proportional: <math>\frac{AA'}{A'D'} = \frac{D'C'}{C'E} \Longrightarrow \frac{1 - s}{s} = \frac{s}{1 - s - CE}</math>. Simplifying, we get that <math>s^2 = (1 - s)(1 - s - CE)</math>. | Call the vertices of the new square A', B', C', and D', in relation to the vertices of <math>ABCD</math>, and define <math>s</math> to be one of the sides of that square. Since the sides are [[parallel]], by [[corresponding angles]] and AA~ we know that triangles <math>AA'D'</math> and <math>D'C'E</math> are similar. Thus, the sides are proportional: <math>\frac{AA'}{A'D'} = \frac{D'C'}{C'E} \Longrightarrow \frac{1 - s}{s} = \frac{s}{1 - s - CE}</math>. Simplifying, we get that <math>s^2 = (1 - s)(1 - s - CE)</math>. | ||
− | <math>\angle EAF</math> is <math>60</math> degrees, so <math>\angle BAE = \frac{90 - 60}{2} = 15</math>. Thus, <math>\cos 15 = \cos (45 - 30) = \frac{\sqrt{6} + \sqrt{2}}{4} = \frac{1}{AE}</math>, so <math>AE = \frac{4}{\sqrt{6} + \sqrt{2}} \cdot \frac{\sqrt{6} - \sqrt{2}}{\sqrt{6} - \sqrt{2}} = \sqrt{6} - \sqrt{2}</math>. Since <math>\triangle AEF</math> is [[equilateral]], <math>EF = AE = \sqrt{6} - \sqrt{2}</math>. <math>\triangle CEF</math> is a <math>45-45-90 \triangle</math>, so <math>CE = \frac{AE}{\sqrt{2}} = \sqrt{3} - 1</math>. Substituting back into the equation from the beginning, we get <math>s^2 = (1 - s)(2 - \sqrt{3} - s)</math>, so <math>(3 - \sqrt{3})s = 2 - \sqrt{3}</math>. Therefore, <math>s = \frac{2 - \sqrt{3}}{3 - \sqrt{3}} \cdot \frac{3 + \sqrt{3}}{3 + \sqrt{3}} = \frac{3 - \sqrt{3}}{6}</math>, and <math>a + b + c = 3 + 3 + 6 = | + | <math>\angle EAF</math> is <math>60</math> degrees, so <math>\angle BAE = \frac{90 - 60}{2} = 15</math>. Thus, <math>\cos 15 = \cos (45 - 30) = \frac{\sqrt{6} + \sqrt{2}}{4} = \frac{1}{AE}</math>, so <math>AE = \frac{4}{\sqrt{6} + \sqrt{2}} \cdot \frac{\sqrt{6} - \sqrt{2}}{\sqrt{6} - \sqrt{2}} = \sqrt{6} - \sqrt{2}</math>. Since <math>\triangle AEF</math> is [[equilateral]], <math>EF = AE = \sqrt{6} - \sqrt{2}</math>. <math>\triangle CEF</math> is a <math>45-45-90 \triangle</math>, so <math>CE = \frac{AE}{\sqrt{2}} = \sqrt{3} - 1</math>. Substituting back into the equation from the beginning, we get <math>s^2 = (1 - s)(2 - \sqrt{3} - s)</math>, so <math>(3 - \sqrt{3})s = 2 - \sqrt{3}</math>. Therefore, <math>s = \frac{2 - \sqrt{3}}{3 - \sqrt{3}} \cdot \frac{3 + \sqrt{3}}{3 + \sqrt{3}} = \frac{3 - \sqrt{3}}{6}</math>, and <math>a + b + c = 3 + 3 + 6 = \boxed{12}</math>. |
---- | ---- | ||
Line 58: | Line 58: | ||
<math>(s-0) = (1 - (\frac{1}{2-\sqrt{3}})s)</math> | <math>(s-0) = (1 - (\frac{1}{2-\sqrt{3}})s)</math> | ||
− | Solving for s, <math>s = \frac{3 - \sqrt{3}}{6}</math>, and <math>a + b + c = 3 + 3 + 6 = | + | Solving for s, <math>s = \frac{3 - \sqrt{3}}{6}</math>, and <math>a + b + c = 3 + 3 + 6 = 12</math>. |
+ | |||
+ | == Solution 3 == | ||
+ | Suppose <math>\overline{AB} = \overline{AD} = x.</math> Note that <math>\angle EAF = 60</math> since the triangle is equilateral, and by symmetry, <math>\angle BAE = \angle DAF = 15.</math> Note that if <math>\overline{AD} = x</math> and <math>\angle BAE = 15</math>, then <math>\overline{AA'}=\frac{x}{\tan(15)}.</math> Also note that <cmath>AB = 1 = \overline{AA'} + \overline{A'B} = \frac{x}{\tan(15)} + x</cmath> | ||
+ | Using the fact <math>\tan(15) = 2-\sqrt{3}</math>, this yields <cmath>x = \frac{1}{3+\sqrt{3}} = \frac{3-\sqrt{3}}{6} \rightarrow 3 + 3 + 6 = \boxed{12}</cmath> | ||
==Elegant Solution== | ==Elegant Solution== | ||
− | Why not solve in terms of the side <math>x</math> only (single-variable beauty)? By similar triangles we obtain that <math>BE=\frac{x}{1-x}</math>, therefore <math>CE=\frac{1-2x}{1-x}</math>. Then <math>AE=\sqrt{2}*\frac{1-2x}{1-x}</math>. Using Pythagorean Theorem on <math>\triangle{ABE}</math> yields <math>\frac{x^2}{(1-x)^2} + 1 = 2 * \frac{(1-2x)^2}{(1-x)^2}</math>. This means <math>6x^2-6x+1=0</math>, and it's clear we take the smaller root: <math>x=\frac{3-\sqrt{3}}{ | + | Why not solve in terms of the side <math>x</math> only (single-variable beauty)? By similar triangles we obtain that <math>BE=\frac{x}{1-x}</math>, therefore <math>CE=\frac{1-2x}{1-x}</math>. Then <math>AE=\sqrt{2}*\frac{1-2x}{1-x}</math>. Using Pythagorean Theorem on <math>\triangle{ABE}</math> yields <math>\frac{x^2}{(1-x)^2} + 1 = 2 * \frac{(1-2x)^2}{(1-x)^2}</math>. This means <math>6x^2-6x+1=0</math>, and it's clear we take the smaller root: <math>x=\frac{3-\sqrt{3}}{6}</math>. Answer: <math>\boxed{12}</math>. |
+ | == Solution 5 (First part is similar to Solution 2) == | ||
+ | Since <math>AEF</math> is equilateral, <math>AE=EF</math>. Let <math>BE=x</math>. By the [[Pythagorean theorem]], <math>1+x^2=2(1-x)^2</math>. Simplifying, we get <math>x^2-4x+1=0</math>. By the quadratic formula, the roots are <math>2 \pm \sqrt{3}</math>. Since <math>x<1</math>, we discard the root with the "+", giving <math>x=2-\sqrt{3}</math>. | ||
+ | <asy> | ||
+ | real n; | ||
+ | n=0.26794919243; | ||
+ | real m; | ||
+ | m=0.2113248654; | ||
+ | draw((0,0)--(0,n)--(1,0)--(0,0)); | ||
+ | draw((0,m)--(m,m)--(m,0)); | ||
+ | label((0,0), "$B$",SW); | ||
+ | label((0,n), "$E$",SW); | ||
+ | label((0,m), "$M$",SW); | ||
+ | label((1,0), "$A$",SW); | ||
+ | label((m,0), "$N$",SW); | ||
+ | label((m,m), "$K$",NE); | ||
+ | </asy> | ||
+ | Let the side length of the square be s. Since <math>MEK</math> is similar to <math>ABE</math>, <math>s=\frac{2-\sqrt{3}-s}{2-\sqrt{3}}</math>. Solving, we get <math>s=\frac{3-\sqrt{3}}{6}</math> and the final answer is <math>\boxed{012}</math>. | ||
== See also == | == See also == |
Latest revision as of 11:23, 8 April 2024
Contents
Problem
Square has sides of length 1. Points and are on and respectively, so that is equilateral. A square with vertex has sides that are parallel to those of and a vertex on The length of a side of this smaller square is where and are positive integers and is not divisible by the square of any prime. Find
Solution 1
Call the vertices of the new square A', B', C', and D', in relation to the vertices of , and define to be one of the sides of that square. Since the sides are parallel, by corresponding angles and AA~ we know that triangles and are similar. Thus, the sides are proportional: . Simplifying, we get that .
is degrees, so . Thus, , so . Since is equilateral, . is a , so . Substituting back into the equation from the beginning, we get , so . Therefore, , and .
Here's an alternative geometric way to calculate (as opposed to trigonometric): The diagonal is made of the altitude of the equilateral triangle and the altitude of the . The former is , and the latter is ; thus . The solution continues as above.
Solution 2
Since is equilateral, . It follows that . Let . Then, and .
.
Square both sides and combine/move terms to get . Therefore and . The second solution is obviously extraneous, so .
Now, consider the square ABCD to be on the Cartesian Coordinate Plane with . Then, the line containing has slope and equation .
The distance from to is the distance from to .
Similarly, the distance from to is the distance from to .
For some value , these two distances are equal.
Solving for s, , and .
Solution 3
Suppose Note that since the triangle is equilateral, and by symmetry, Note that if and , then Also note that Using the fact , this yields
Elegant Solution
Why not solve in terms of the side only (single-variable beauty)? By similar triangles we obtain that , therefore . Then . Using Pythagorean Theorem on yields . This means , and it's clear we take the smaller root: . Answer: .
Solution 5 (First part is similar to Solution 2)
Since is equilateral, . Let . By the Pythagorean theorem, . Simplifying, we get . By the quadratic formula, the roots are . Since , we discard the root with the "+", giving . Let the side length of the square be s. Since is similar to , . Solving, we get and the final answer is .
See also
2006 AIME II (Problems • Answer Key • Resources) | ||
Preceded by Problem 5 |
Followed by Problem 7 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.